Protocolo de fotogrametria computadorizada na quantificacao angular da escoliose - Rozilene Maria Cota Aroeira (2009)
The scoliosis is a three-dimensional deformation of the spine. It is a serious disease that can compromise vital organs like heart and lungs, in addition to influence the aesthetic and quality of life. His progression is generally associated with growth peak, getting in that case, the name of the adolescent idiopathic scoliosis (AIS). Thus, the pubertal period is one where there is greater need for medical care and physiotherapy. The e X-rays are, for decades, the examination of choice for measurement and monitoring of the deformity and is recommended up to four tests per year. Meanwhile, the X-rays are ionizing rays that cause deleterious effects to the body when in repeated doses, such as: cancer, leukemia and genetic effects, these effects extended to non complete bone maturation. Such considerations have led in recent years, several studies of alternative, noninvasive, for measurement and monitoring of scoliosis. This study aimed to develop a protocol of computerized photogrammetry tomeasure the angle of scoliosis. We evaluated 16 patients (14 females and 2 males), holders of AIS, who had to request medical achievement of radiographic examination, panoramic, posteroanterior and profile of the spine and whose averages were age 21,44 ± 6,17, weight 52,91 ± 5,88, height 11,63 ± 0,05 and mass body 19,86 ± 0,26. Anatomic landmarks of the vectorial type were placed on the skin, on the spinous processes of the C7-L5 vertebrae, to permit the identification and spatial orientation of each vertebra, and also was used a revolving plataform created to position the patients in different angles required for postural analysis. Radiologic evaluation was performed with the subject standing, anteroposterior and profile ( 90º) and, soon after, the subject were photographed with a digital camera in the frontal posterior plane, right and left sagittal planes in the angles of 45º and 90º. The photographic images, in the frontal posterior plane, were subjected to analysis of the angles and identification from apical vertebra by the method proposed in this study, using the software CorelDraw13®. The radiographs were subjected to analysis of the angles by the Cobb method and identification from apical vertebra. The angles obtained by computerized photogrammetry were compared with those obtained by the Cobb method. According to the descriptive statistics, we can say that there was no statistically significant difference (p-value < 5%) between the measurements for both methods, for thoracic and lumbar curves. Also,there was no statistically significant difference (p-value > 5%) for identification from apical vertebra, on the two segments from spinal column, among the method concerning x-rays & the method proposed in this study. The demonstration presented mathematics is consistent86 and demonstrated the equivalence between the Cobb method and method proposed in this study. The proposed methodology is unique in all stages of the protocol creating a new approach in the quantification of angular scoliosis by noninvasive method.